2018
DOI: 10.1016/j.neuron.2018.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of the Mouse Brain Synaptome

Abstract: SummarySynapses are found in vast numbers in the brain and contain complex proteomes. We developed genetic labeling and imaging methods to examine synaptic proteins in individual excitatory synapses across all regions of the mouse brain. Synapse catalogs were generated from the molecular and morphological features of a billion synapses. Each synapse subtype showed a unique anatomical distribution, and each brain region showed a distinct signature of synapse subtypes. Whole-brain synaptome cartography revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
398
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 210 publications
(416 citation statements)
references
References 91 publications
18
398
0
Order By: Relevance
“…In this study, the levels of VGLUT2 and PSD95 were found to be significantly higher in the mPFC than in the pCG, while the VGLUT1 levels were found to be similar between the two regions. Similar results have been reported in previous studies . The mPFC of rodents was also shown to have higher expressions of synaptojanin 2 binding protein and NMDA receptors, relative to the pCG.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, the levels of VGLUT2 and PSD95 were found to be significantly higher in the mPFC than in the pCG, while the VGLUT1 levels were found to be similar between the two regions. Similar results have been reported in previous studies . The mPFC of rodents was also shown to have higher expressions of synaptojanin 2 binding protein and NMDA receptors, relative to the pCG.…”
Section: Discussionsupporting
confidence: 90%
“…Similar results have been reported in previous studies. 37,38 The mPFC of rodents was also shown to have higher expressions of synaptojanin 2 binding protein 39 and NMDA receptors, 40 relative to the pCG. All these lines of evidence suggested that, relative to the pCG, the mPFC may have a higher density of glutamatergic terminals, especially those originating from the subcortical nuclei.…”
Section: Glu and Glxmentioning
confidence: 98%
“…Brain‐wide catalogs of synaptic information may allow for data mining and systematic hypothesis testing. A recent high‐throughput genetic imaging study in the mouse, for instance, ascribed a high degree of synaptic diversity to the hippocampal formation, possibly associated with its specific cognitive functions (F. Zhu et al, ). However, efforts in this direction have so far largely focused on molecular features (O'Rourke, Weiler, Micheva, & Smith, ; Paul et al, ; Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…), and diversification of molecular machineries subserving neuronal signaling (Grant ; Zhu et al. ), all contribute to the broad behavioral repertoires seen in various vertebrates. Because quantitative mapping of cell type and synaptic density distributions across the brain is challenging and difficult to interpret, and because consequences of cellular and molecular diversification for cognitive processes remain poorly understood, here we focus on the number of neurons, which currently is the most feasible, easy‐to‐measure proxy for cognitive abilities.…”
mentioning
confidence: 99%
“…Other factors at play include the number of neuronal connections, neuron packing density, interneuronal distance, and axonal conduction velocity (Dicke and Roth 2016). Thus, besides the total number of neurons and their connections, diversification of neuronal types and their properties (Markram et al 2015;Tasic et al 2018;Tosches et al 2018;Zeisel et al 2018), and diversification of molecular machineries subserving neuronal signaling (Grant 2016;Zhu et al 2018), all contribute to the broad behavioral repertoires seen in various vertebrates. Because quantitative mapping of cell type and synaptic density distributions across the brain is challenging and difficult to interpret, and because consequences of cellular and molecular diversification for cognitive processes remain poorly understood, here we focus on the number of neurons, which currently is the most feasible, easy-to-measure proxy for cognitive abilities.…”
mentioning
confidence: 99%